Pengembangan Media Pembelajaran Berbasis Canva pada Materi Teks Diskusi Peserta Didik Kelas XI SMP Al-Falah - Syahrul Kirom; Hosniyeh; Muhammad Masykur Baiquni (Lembaga Penerbitan dan Publikasi Ilmiah (LP2I), 2025)
The aim of this research is development to increase students' learning motivation at Al Falah Gondanglegi Middle School. This learning media is made based on material that is adapted to students' level of thinking, so that students no longer have difficulty understanding the material presented in learning, especially discussion texts. This type of research uses research and development (R&D) methods in this research using five steps, namely analysis, planning, development, implementation and evaluation which produces a product and then tests the effectiveness of the product. This research develops learning media using the Canva application for discussion text material for middle school class IX. The results of research on media expert validation obtained a percentage of 72.5%. with a very good/valid category. This means that learning media using the Canva application is suitable/valid for use in learning. Then the level of effectiveness of learning media using the Canva application increases students' learning motivation. Motivation before using the media (pre test) and after using the media (post test) obtained a difference/comparison value of 84 and 89. Based on the results of the comparison of the two, using the N-Gain formula the value obtained was 0.31 in the good category/ effective enough.